Conflicting Requirements for Transparency and Mechanical Stability in the Compound Eyes of Desert Locusts. Issue 27 (26th August 2022) - Li, Chuchu; Rajabi, Hamed; Gorb, Stanislav N.
Abstract: Compound eyes of insects should be both thin and transparent to allow light to pass through, and at the same time mechanically stable to serve as exoskeleton. These conflicting requirements make the corneal cuticle an interesting example for studying cuticle biomechanics as well as for designing composite materials that seek similar properties. Here, scanning electron microscopy, confocal laser scanning microscopy, and nanoindentation are combined to investigate the microstructure, material composition, and material properties of the corneal cuticle of desert locust Schistocerca gregaria . The results suggest that a fully helicoidal architecture and large proportion of resilin in the corneal cuticle are likely to be adaptations for light transmission. Even though the corneal cuticle is resilin‐rich, its elastic modulus is at least three times higher than that previously reported for other resilin‐rich cuticles. This is likely due to the specific microstructure of the corneal cuticle with densely packed layers. This study presents one of a series of studies, in which multidisciplinary approaches are used to understand the link between the structure, material, property, and function in insect cuticle. Abstract : The mechanics of locust corneal cuticle underlying two conflicting functions is investigated. Combination of the large resilin proportion and dense helicoidal architecture enables the corneal cuticle to satisfy both functions of vision and mechanical stability. This study helps to shed light on the biomechanics of the complex composite material of insect cuticle.